2016
DOI: 10.5194/we-16-97-2016
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of floristic composition of the abandoned Cu-dump field Piesky (Staré Hory Mountains, Slovakia)

Abstract: Abstract. The Cu-dump field Piesky is an important historical abandoned mining area in the region of central Europe, well known for the high content of heavy metals in its soil, especially copper, the content of which varies from 933.40 to 1485.40 mg kg−1. Floristic and phytosociological research was carried out here during the vegetation seasons in 2011–2014. Altogether a total of 156 taxa of vascular plants were found. The most common species were Acetosella vulgaris, Agrostis capillaris, A. stolonifera, Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the literature, we did not find data on the species composition and vegetation structure of slag dumps, but the floristic composition was studied for abandoned copper ore deposits (Zheleva et al, 2012;Turisova et al, 2016). Phytocenotic studies of the Elatsite copper-porphyry deposit dumps (Bulgaria) revealed 55 plant species, of which 32 are weeds.…”
Section: Zolotova 2021mentioning
confidence: 98%
See 1 more Smart Citation
“…In the literature, we did not find data on the species composition and vegetation structure of slag dumps, but the floristic composition was studied for abandoned copper ore deposits (Zheleva et al, 2012;Turisova et al, 2016). Phytocenotic studies of the Elatsite copper-porphyry deposit dumps (Bulgaria) revealed 55 plant species, of which 32 are weeds.…”
Section: Zolotova 2021mentioning
confidence: 98%
“…The heavy metals content in the technogenic soil of old abandoned deposit Pieski (Slovakia) remains high (copper concentration from 933.40 to 1485.40 mg kg -1 ), under these conditions 156 taxa of vascular plants were found. The most common species are Acetosella vulgaris, Agrostis capillaries and A. Stolonifera, Arabidopsis arenosa, and Festuca rubra (Turisova et al, 2016).…”
Section: Zolotova 2021mentioning
confidence: 99%
“…In light of increasing ecological awareness, spontaneous flora that were once viewed as ‘weeds’ have begun to gain attention for the variety of positive attributes they offer ( Kondratenko et al 2022 ). The native pioneers’ flora have the potential to control erosion in storage facilities, stabilize those facilities through a root net system and moderate floods, as well as enhance surface moisture and improve the content of organic matter ( Bateman et al 2021 , Turisová et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The richness and diversity of plant species play an important role in assessing the success of a restoration project (Solomou et al, 2023). Plant communities in spontaneous revegetation of abandoned lands contamina-ted with heavy metals were evaluated in terms of their syntaxonomic structure and Ellenberg's indicator scales (Turisová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%